Gestational diabetes (Research, Society and Development, 2022)
Gestational diabetes mellitus (GDM) is considered a public health problem. It is a disease that is characterized by an increase in blood sugar, whose onset occurs during pregnancy, and may or may not persist after pregnancy. Among the factors related to the development of gestational diabetes, advanced maternal age can be mentioned. This pathology does not show many symptoms, so for its identification it is necessary some fasting glucose tests, oral glucose tolerance test (OGTT) and glycated hemoglobin, among others. Gestational diabetes can bring complications for the mother and fetus, as well as obesity, fetal hyperglycemia or hypoglycemia, and excessive fetal growth. It is extremely important to have an adequate medical follow-up for a good evolution of the case, being able to resort to diets and physical activities or even the use of medication. In this context, an integrative review was carried out in order to show the complications that can occur in patients with GDM, the care and treatments recommended during pregnancy and postpartum.